The Effect Of Fundamental And External Factors On Stock Returns With Inflation As A Mediator An Explanatory Study Of Banking Companies In The Banking Group Based On Core Capital - Muhamad Kadafi; Ghozali Maski; Tyas Danarti Hascaryani (Academic Bright Collaboration, 2026)
Purpose – This study examines the direct effects of Return on Equity (ROE), Capital Adequacy Ratio (CAR), Debt-to-Equity Ratio (DER), Composite Stock Price Index (CSPI), exchange rate, and deposit interest rates on the stock returns of Indonesian KBMI 4 banks, while testing inflation as a mediating variable. Methods – An explanatory quantitative design was applied to four KBMI 4 banks BRI, BNI, Mandiri, and BCA using saturated sampling and 56 observations. Secondary data were obtained from annual financial reports, Indonesian banking statistics, the Financial Services Authority, and the Indonesia Stock Exchange. Panel data were analyzed using Stata 17 through model-selection tests, classical assumption tests, hypothesis testing, and the Aroian version of the Sobel test. Findings – The independent variables jointly explained 30.76% of stock-return variation. External factors were the primary determinants. CSPI had a significant positive effect (p = 0.004), the exchange rate had a significant negative effect (p = 0.002), and deposit interest rates had a significant positive effect (p = 0.009). ROE, CAR, and DER had no significant effects. Inflation significantly affected stock returns in the basic model, but its effect weakened after other variables were included. The Aroian test confirmed that inflation did not mediate any relationships at the 5% significance level. Research Implications – The findings provide insights into the financial condition of KBMI 4 banks, support investor decision-making, and offer a reference for future research. Originality – This study integrates signaling theory, arbitrage theory, and the efficient market hypothesis, while uniquely examining inflation as a mediator of stock returns among Indonesia’s largest banks.